NEGOTIATING MOTHERHOOD IN CONSTRAINING SPACE IN EMMA DONOGHUE’S ROOM - Putti Aisyah; Hujuala Rika Ayu (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This study sheds light on how Ma, the female character in Emma Donoghue’s Room negotiates her roles as a mother of a five-years-old Jack while living inside a constraining room built by Nick, her kidnapper. It particularly focuses on how Ma attempts to re-define her motherhood within built and discursive spaces that Nick constructs. The study employs the concepts of Sarah Ruddick on maternal thinking and Marsha Marotta’s MotherSpace. Marrota delineates two spatial aspects contributing to shape mother’s subjectivity; built spaces and discursive spaces. Built space is the 11x11m room representing Nick’s authority. Nick also partly constructs the discursive space within the room. The finding shows that Ma is able to create her own discursive space as her effort of conforming her motherhood, within the constraining built space. Ma successfully performs her sense of motherhood – such as providing him physical needs like nutritious food and nurturing his cognitive development.